Urbanization and Its Environmental Impact on Human Beings in Nepal - Acharya, Sharad (International Research Journal of MMC, 2025)
Urbanization, marked by population growth and industrial development, has led to significant social, economic, and environmental transformations worldwide, including in Nepal. This study examines the impacts of urbanization on the environment and society in Nepal, with a particular focus on the Kathmandu Valley. It investigates how urbanization impacts human well-being in Nepal through a non-empirical, desk-based approach that reviews sources of secondary data. The rapid and often unplanned urbanization in Nepal, fueled by migration, economic opportunities, and changes in policy, has created both advantages and challenges. While urbanization has driven economic growth and enhanced access to education, healthcare, and various services, it has also resulted in deforestation, loss of biodiversity, air and water pollution, and inadequate waste management, leading to serious public health concerns and environmental decline. The study highlights socio-economic inequality, poor housing conditions, and insufficient infrastructure as major challenges associated with urbanization. The findings underscore the necessity for sustainable urban development strategies, which should include improved urban planning, public health initiatives, and effective environmental management practices. Tackling these challenges is essential for balancing economic growth, environmental protection, and social equity. The study stresses the urgent need to address the negative impacts of urbanization on Nepal’s ecosystems and natural resources, providing insights into sustainable urban practices that can inform future policy decisions.